Revisão criminal - SANTOS, Daiane da Cruz; AUBANO, Janaina Elena; BERTUCCI, Tauane (060, 2022)
A revisão criminal é uma ação autônoma de impugnação que se presta a rescindir, no todo ou em parte, a coisa julgada penal ( sentença ou acórdão condenatório ). Cumpre, pois, o mesmo papel da ação rescisória no processo civil. E tem uma dupla finalidade: revisar uma injusta condenação e proteger a dignidade do condenado. Embora a doutrina costume vincular a revisão ao erro juriciário, tal não é de todo exato, visto que há hipótese de revisão que nada têm a ver com isso ( v.g., abolitio criminis). O erro judiciário é o principal fundamento da rescisão da res judicata penal, mas não o único.

Criminal review is an autonomous action of challenge that lends itself to rescinding, in whole or in part, the criminal res judicata (convicting sentence or judgment). It therefore fulfills the same role as the rescissory action in civil proceedings. and has a dual purpose: to review an unjust conviction and to protect the condemned's dignity. although the doctrine usually links the review to the miscarriage of justice, this is not entirely accurate, since there are hypotheses of review that have nothing to do with it (e.g., abolitio criminis ). Judicial error is the main reason for terminating the criminal res judicata, but not the only one.
criminal review
Keywords: Erro judiciário; Gestão e Negócios